From Western Asia to the Mediterranean Basin: Diversification of the Widespread Euphorbia nicaeensis Alliance (Euphorbiaceae) - Stojilkovič, Valentina; Záveská, Eliška; Frajman, Božo (Frontiers in Plant Science, 2022)
The Mediterranean Basin is an important biodiversity hotspot and one of the richest areas in the world in terms of plant diversity. Its flora parallels in several aspects that of the Eurasian steppes and the adjacent Irano-Turanian floristic region. The E. nicaeensis alliance spans this immense area from the western Mediterranean to Central Asia. Using an array of complementary methods ranging from phylogenomic and phylogenetic data through relative genome size (RGS) estimation to morphometry, we explored relationships and biogeographic connections among taxa of this group. We identified the main evolutionary lineages, which mostly correspond to described taxa. However, despite the use of highly resolving RAD sequencing data, relationships among the main lineages remain ambiguous. This is likely due to hybridisation, lineage sorting triggered by rapid range expansion, and polyploidisation. The phylogenomic data identified cryptic diversity in the Mediterranean, which is also correlated with RGS and partly also morphological divergence, rendering the description of a new species necessary. Biogeographic analyses suggest that Western Asia is the source area for the colonisation of the Mediterranean by this plant group and highlight the important contribution of the Irano-Turanian region to the high diversity in the Mediterranean Basin. The diversification of the E. nicaeensis alliance in the Mediterranean was triggered by vicariance in isolated Pleistocene refugia, morphological adaptation to divergent ecological conditions and, to a lesser extent, by polyploidisation.